L’innovation à l’épreuve de l’anthropocène. Compte rendu de lecture de L’Innovation, mais pour quoi faire ? de Franck Aggeri - Agnès Labrousse (Revue de la Régulation)
In this incisive, interdisciplinary book on innovation, Franck Aggeri gives pride of place to the critical social sciences—critical management studies, institutional economics, sociology of innovation, environmental history etc.—to deconstruct some of the myths surrounding innovation. By historicising a number of concepts, practices and imaginaries, he helps us to move away from techno-solutionism without lapsing into technophobia. Attention to the mechanisms, indicators and other instruments of management in use is part of the contribution of a managerial-but-not-only perspective. This critical essay reviews the book’s main contributions and suggests a number of nuances, additions and extensions to revisit the history (of thought) of innovation, further integrate some of the contributions of ecological economics or contribute to decolonising the imaginaries of innovation. It shows that Aggeri’s opus offers a highly relevant synthesis for rethinking innovation in the face of the Anthropocene, shedding light on the dark side of innovation and then outlining ways of innovating differently and better.